La exégesis bíblica en la polémica contra judíos - Manuel Montoza Coca (Mélanges de la Casa de Velázquez, 2019)
In the year 1520, Don Martin Garcia gathered and printed a selection of 156 of his sermons, the main objective of which was both political and religious. The composition of these sermons took place between the years 1490 and 1510, when the politics of the king Ferdinand of Aragon and the queen Isabella of Castile were aimed to unify all the different Hispanic kingdoms under the Catholic faith. For that purpose, preachers like Don Martin Garcia wrote, delivered and published works whose main goal was to definitely convert those who were reluctant to adopt the Christian faith and also to consolidate the beliefs of those who were already Christians. This paper shows the use of the exegesis and the analysis of different sacred texts aimed to persuade, convince and defeat the «adversary» through a reasoning based on the proof of the Sacred Scriptures. As an example of this system, I will study the structure of the 14th sermon of Martin Garcia's compilation.